(untitled) (Modern education and development, 2025)
In the modern world, English has become an important tool for Global Communication and knowledge exchange. The application of modern technology in the English language learning process, on the other hand, makes it possible to provide students with a more efficient and interesting education. In this article, we will talk about the advantages, methods of teaching and future prospects for the integration of English and modern technologies.